The European free-tailed bat, Tadarida teniotis, in a suburban area of Latina, Latium (Central Italy) / Il Molosso di Cestoni, Tadarida teniotis, nell'ambiente suburbano di Latina, Lazio (Italia centrale) - Luigi Corsetti (Hystrix, the Italian Journal of Mammalogy, 1990)
Abstract Since April 1983 to March 1990, the author carried out observations on the European free-tailed bat (Tadarida teniotis) in a suburban house of Latina. The shelter used by the species was located between the outer wall and the flue of the central heating system. The maximum number of specimens observed at the same time was one male and two females. Some characteristic calls uttered by the male have been noticed. These consisted in several very loud shrill notes often given out in rapid succession. These calls have been heard mainly during the day and at sunset, amid the noise from the city and industries in the surrounding; they lasted about 30 seconds on average (up to 45). These calls were probably given out at times of maximum excitement, perhaps in the pre-mating phase. They were heard more frequently in spring (March-May) but also in autumn (October-November). Flight generally occurred at temperatures no lower than 16 °C and from 25 to 60 minutes after sunset, after characteristic loud calls, and coming its habitual shelter. The presence of the European free-tailed bat in this spot may have been influenced by the source of heat represented by the flue, which supplied warmth during the winter months and, at the same time, by the trophic opportunities offered by the vast uncultivated fields in the area, with luxuriant herbaceous vegetation, scattered shrubs and trees, ditches, a few small cane thickets, flooded fields. The flue has not been activated since 1987, but the species has continued to live in the same place until 1590 (last sighting on March 1). The author excludes the presence of the species in the study site before 1983. Riassunto Dall'aprile 1983 al marzo 1990 l'autore ha compiuto osservazioni sul Molosso di Cestoni (Tadarida teniotis), in un'abitazione alla periferia della città di Latina. I1 ricovero abituale della specie è localizzato tra il muro esterno e la canna fumaria dell'impianto centralizzato di riscaldamento. I1 numero massimo di esemplari osservati contemporaneamente è stato di un maschio e due femmine. Sono stati rilevati alcuni caratteristici richiami emessi dal maschio in momenti di massima eccitazione, probabilmente nelle fasi pre-copula, principalmente nei mesi primaverili (marzo-maggio) ma anche autunnali (ottobre-novembre). L'involo si è verificato generalmente con temperature dell'aria non inferiori ai 16 °C e da 25 a 60 minuti dopo il tramonto, eccetto in un caso dove un esemplare in volo, alto e diritto, è stato osservato pochi minuti dopo il tramonto del sole e dopo aver ascoltato i forti richiami provenienti dal ricovero abituale della specie.